The hunting moon - Dennard, Susan (The Luminaries., 2023)
After passing the hunter trials and gaining local celebrity status, Winnie Wednesday struggles to prove the innocence of a wrongly accused werewolf and the existence of a sinister force called the Whisperer, while she unravels the mysteries surrounding her family's magic which leads her to question her loyalties and Luminary heritage.